2002
DOI: 10.1103/physreva.65.043402
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-fluid-dynamics approach for strong-field processes: Application to the study of multiphoton ionization and high-order harmonic generation of He and Ne atoms in intense laser fields

Abstract: We explore the feasibility of extending the quantum-fluid dynamics ͑QFD͒ approach for quantitative investigation of nonlinear optical processes of many-electron quantum systems in intense laser fields. Through the amalgamation of the QFD and density-functional theory ͑DFT͒, a single time-dependent hydrodynamical equation of motion can be derived. This equation has the form of a generalized nonlinear Schrödinger equation ͑GNLSE͒ but includes the many-body effects through a local time-dependent exchange-correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…It has also been observed that the algorithm is [39]. The values at the boundaries required for the solution are obtained through equation (17).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been observed that the algorithm is [39]. The values at the boundaries required for the solution are obtained through equation (17).…”
Section: Resultsmentioning
confidence: 99%
“…The QFD-DFT approach had been subsequently used to obtain the ground-state densities in spherical coordinates [10][11][12] as well as to study dynamical properties of two-electron systems [13][14][15][16]. There has also been an abiding interest in studying the static and dynamic properties of noble gas atoms and clusters, especially the phenomenon of above-threshold ionization (ATI), high-order harmonic generation (HHG), unusual stabilization, etc, in intense laser fields [17][18][19][20][21]. The QFD-DFT approach has been tested on such systems to study their ground-state properties by Roy and Chu [12] using a time-dependent generalized pseudospectral technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By means of an optimal, non-uniform spatial grid, it leads to a symmetric eigenvalue problem, which can be easily solved by standard diagonalization routines available. It has been applied to a series of model and real systems, in both free and confined cases, viz., spiked harmonic oscillators [61,70], powerlaw and logarithmic [62], Húlthen and Yukawa [64], Hellmann [68], rational [69], exponential-screened Coulomb [71], Morse [72], hyperbolic [73], Deng-Fan [74], Manning-Rosen [75], Tietz-Hua [76], other singular [65] potentials, as well as many-electron systems within the broad domain of DFT [95,96,88,63,66,67]. Of late this has also produced excellent quality results in various radial confinement [46,47,77,78] studies in several Coulombic systems, as well as in 3DCHO.…”
Section: Generalized Pseudospectral (Gps) Methodsmentioning
confidence: 99%
“…8,9) The GPS method is capable of providing high-precision wave functions through a nonuniform spatial-grid discretization procedure. 9) As a result, Roy obtained the energy eigenvalues for systems with a wide range of coupling parameter.…”
Section: Introductionmentioning
confidence: 99%